2015
DOI: 10.1016/j.biomaterials.2015.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Nerve guides manufactured from photocurable polymers to aid peripheral nerve repair

Abstract: The peripheral nervous system has a limited innate capacity for self-repair following injury, and surgical intervention is often required. For injuries greater than a few millimeters autografting is standard practice although it is associated with donor site morbidity and is limited in its availability. Because of this, nerve guidance conduits (NGCs) can be viewed as an advantageous alternative, but currently have limited efficacy for short and large injury gaps in comparison to autograft. Current commercially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 58 publications
2
153
0
Order By: Relevance
“…The genetic modification enabling this fluorescence has no influence upon regeneration and no harmful effects have been reported [33]. In terms of axon visualization, graft repair controls were comparable to previous studies, with areas of axon disruption located between the graft and nerve ends and fairly organized axons within the graft tissue itself [31]. PGSm repairs displayed observably fewer axons overall, with axons occupying a thin strip between nerve endings -correlating to the above observations of the harvested tissue.…”
Section: In Vivo Common Fibular Nerve Regeneration Analysissupporting
confidence: 71%
See 3 more Smart Citations
“…The genetic modification enabling this fluorescence has no influence upon regeneration and no harmful effects have been reported [33]. In terms of axon visualization, graft repair controls were comparable to previous studies, with areas of axon disruption located between the graft and nerve ends and fairly organized axons within the graft tissue itself [31]. PGSm repairs displayed observably fewer axons overall, with axons occupying a thin strip between nerve endings -correlating to the above observations of the harvested tissue.…”
Section: In Vivo Common Fibular Nerve Regeneration Analysissupporting
confidence: 71%
“…This issue was overcome by using laser cutting post-production, creating precisely designed highly reproducible conduits. The NGCs were elastic in nature, and when bent did not fracture or kink, making them easier to handle surgically than previously studied stiff polyethylene glycol (PEG) conduits, which exhibited a stiffness of 470 MPa as compared to 3.2 MPa for the PGSm NGCs in this study [31].I ti s reported that kinking of NGC's may occlude the conduit lumen, hindering axonal regeneration, particularly with larger gap injuries [40]. It is therefore advantageous for a conduit to flex with body movements before kinking.…”
Section: Tablementioning
confidence: 65%
See 2 more Smart Citations
“…The printing process did not affect the viability of the RGC/glial cells in culture, and retain the growth promoting properties of the glial cells. Pateman et al 55 printed PEG-based fine nerve guidance conduit through microstereo lithographic technique for nerve repair studies. In addition, 4D bioprinting has also been applied in several studies, for example bone tissue, 56 vascular tissue 21,41,57,58 etc.…”
Section: 28-30mentioning
confidence: 99%